Socialization of Tempeh as Organic and Healthy Food for Household Mother in The South Tangerang City - Anastasi Tatik Hartanti; Yasinta Ratna Esti Wulandari; Rory Anthony Hutagalung; Tati Barus (Institute for Research and Community Services, 2018)
Tempeh is a traditional Indonesian food that has many advantages as food and the process of making it is quite simple. However, the community knowledge about tempeh and the skills to produce healthy tempeh are still low. This community service aimed to increase the knowledge about tempeh and to improve the skills of its manufacturers in making healthy and good quality tempeh. The activities were carried out for mothers living in Villa Dago Tol complex, Ciputat, South Tangerang 15414, by using the methods of counseling, demonstration, and mentoring. Monitoring was conducted to measure the success rate of participants in producing healthy tempeh. The level of community knowledge about tempeh was evaluated through survey method. The results of counseling, demonstration, and mentoring succeeded in improving the participant skills as seen from the participants' success in following the healthy tempeh-making procedure. The results were also reinforced by the results of monitoring where all participants managed to create healthy tempeh. Survey results showed participants’ increasing knowledge of healthy tempeh and motivation in producing healthy tempeh. Assessment of participants showed good results, especially in improving knowledge (73% stated strongly agree and the rest agree). The ability of the facilitators in delivering the material was also considered good by the participants (92% stated strongly agree and the rest agree). As a follow-up, the participants suggested that the training be extended to the other communities and the training also include a variety of topics such as the manufacturing of tofu, healthy food processing, sewing, and many others.